Impact of heavy metal cations on deposition and release of clay colloids in saturated porous media. Issue 1 (5th January 2022) - Shi, Kaiyu; Wang, Xingrun; Chu, Xianxian; Li, Tiantian; Yin, Yaru; Shen, Chongyang
Abstract: While the facilitated transport of heavy metals by colloids such as clay particles has been widely recognized, the influence of heavy metals on transport of the colloids has received much less attention. This study conducted saturated column experiments to systematically examine influence of multivalent heavy metal cations on transport of natural clay colloids and fullerene n C60 nanoparticles in glass bead porous media. Results showed that the presence of Cd 2+ in the solution can cause more deposition of clay colloids in glass beads compared to Ca 2+ at a given ionic strength (IS), and the subsequent release by IS reduction was less, demonstrating that the presence of Cd 2+ increased the irreversibility of attachment. When the glass beads were initially adsorbed with Ca 2+ and Cd 2+, the release of clay colloids was significantly reduced due to strong cation bridge between the clay colloids and collector surfaces via the heavy metal cations. The release of clay colloids was significantly increased upon reduction of solution IS if the Na + was used to exchange for the Ca 2+ or Cd 2+ before the IS reduction. Additional experiments showed that the n C60 nanoparticles that were deposited in the presence of Fe 3+ and Cu 2+ cannot be released by reduction of solution IS. However, the nanoparticle release occurred when the Ca 2+ was used to exchange for the Fe 3+ and Cu 2+ . Our work was the first to reveal the influence of heavy metal cations on the irreversibility of colloid attachment, and the findings have important implication to fabrication of functional nanomaterials for stabilization of heavy metals in soil and development of mathematic models for accurate prediction of cotransport of heavy metals and colloids in subsurface environments. Core Ideas: Cd 2+ enhanced attachment of clay colloids in porous media compared with Ca 2+ . Cd 2+ increased the irreversibility of attachment of clay colloids compared with Ca 2+ . Preadsorption of the Cd 2+ and Ca 2+ significantly enhanced the attachment irreversibility. The release of clay colloids deposited via Cd 2+ and Ca 2+ was enhanced via cation exchange.